A Brontë Reading List: Part 8. (2nd October 2017) - Ogden, James; Cook, Peter; Pearson, Sara L.
Abstract : This list is part of an annotated bibliography of scholarly and critical work. The earlier parts were published in Brontë Studies, 32.2 (July 2007), 33.3 (November 2008), 34.3 (November 2009), 36.4 (November 2011), 37.3 (September 2012), 39.1 (January 2014) and 41.3 (September 2016). The present part covers work published in 2014.